(untitled) (PAMPA, 2023)
Agroecology emerges, like a science and a practice, as an alternative to the dominant model of agricultural production, based on the use of external inputs of chemical synthesis, and due to its negative effects in environmental and social terms. In the province of Santa Fe (Argentina), there are more every year producers who call themselves agroecological, registered by official surveys and from the consultations they carry out with regional technological organizations. A deeper look at these subjects demanding technical references allows us to observe that, behind said self-identification, there is a diversity of men and women with socio-professional trajectories, available resources and different goals. This work proposes a characterization of a group of producers who call themselves agroecological in the center of Santa Fe that allows the generation of inputs so that regional technological organizations can review the design of public policies and extension strategies.